A zinc ion battery positive electrode material and preparation method thereof
By using Cu@Cu31S16 positive electrode material in zinc ion batteries, the problems of easy dissolution and low energy density of traditional zinc ion batteries are solved, significantly improving the battery's magnification and cycling performance, and having the advantages of economical and easy operation.
Patent Information
- Application Number
- CN202310868255.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-14
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2043-07-14
AI Technical Summary
The cathode materials of traditional zinc ion batteries are prone to the ginger Taylor effect, resulting in electrode dissolution, short battery life and low energy density, so it is necessary to develop a cathode materials with high performance and low cost to improve the performance of zinc ion batteries.
The Cu@Cu31S16 positive electrode material with integrated current collector electrode material without binder and conductive agent was prepared by using the method of in-situ etching of copper foil by polysulfur precursor solution, and was applied to zinc ion batteries to improve capacity and cycling performance.
By using Cu@Cu31S16 positive electrode material, the rate performance and cycle performance of zinc ion batteries have been significantly improved, the first discharge specific capacity reaches a high value, and has the advantages of low production cost and ease of operation.
Smart Images

Figure CN116895754B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of zinc ion batteries, and particularly relates to a zinc ion battery positive electrode material and a preparation method thereof. Background Art
[0002] With the continuous progress of science and technology and society, various electronic devices and power vehicles are developing rapidly, which has led to the continuous increase in people's requirements for energy storage systems. At the same time, the increasing depletion of non-renewable energy and increasingly severe environmental problems have made it more and more urgent to develop a safe and efficient energy storage system. The energy density of traditional secondary batteries has been close to its theoretical limit, but it still cannot meet the needs of human society for high energy density secondary batteries. Since its commercialization, lithium-ion batteries have been favored by people due to their good stability, long cycle life, and portability. However, the theoretical capacity of traditional lithium-ion battery positive electrode materials is low and their cost is high, so their further development is limited.
[0003] In recent years, zinc-ion batteries have become popular due to their high theoretical capacity (820 mAhg -1 、5855 mAh cm -3 ), environmentally friendly, low-cost, abundant in the earth's crust and non-toxic, etc., have attracted widespread attention. And these characteristics can provide a good basic condition for the development of zinc-ion batteries.
[0004] However, the commonly used positive electrode materials for zinc-ion batteries still face many challenges. For example, the commonly used manganese-based positive electrode materials are often prone to the Jan-Taylor effect due to the inherent characteristics of manganese-based materials, resulting in electrode dissolution and inactivation of the materials. These problems such as electrode material dissolution, short battery life, and low energy density need to be solved urgently.
[0005] To address these issues, some high-performance, low-cost cathode materials are needed to improve the performance of zinc-ion batteries. Replacing metal oxides with transition metal sulfides has been considered a feasible approach to address the insufficient rate capability and cycling capacity of zinc-ion batteries. Transition metal sulfides (TMS) are considered promising conversion reaction electrodes with good kinetics due to their relatively weak metal-sulfur bonds that enable efficient conversion. In this family, CuS is a member of the layered TMS with a hexagonal structure consisting of van der Waals-coupled Cu-S tetrahedra with an interlayer spacing of ~8.2Å. This Cu nanostructure provides a large surface area and open channels to facilitate rapid Zn 2+ In addition, Cu has a high electronic conductivity (~103 S cm −1 ), which facilitates the transfer of charges and results in higher energy density and long-term cycling stability.
[0006] Cu-based materials such as CuI, Cu2S, and Cu2O have been shown to be able to undergo conversion reactions in aqueous Zn-ion batteries. Moreover, through the conversion mechanism, Cu-based materials offer high capacity, which can greatly improve the energy density of ZIBs. 31 S 16 There is still a lack of research on positive electrode materials for zinc ion batteries. In view of this, the present invention provides a positive electrode material for zinc ion batteries and a preparation method thereof. Summary of the invention
[0007] The purpose of the present invention is to provide a zinc ion battery positive electrode material and a preparation method thereof to solve the problems raised in the background technology. By applying the positive electrode material to a zinc ion battery, the rate performance and cycle performance of the zinc ion battery are significantly improved.
[0008] In order to achieve the above object, the present invention adopts the following technical solutions:
[0009] The present invention aims to improve the capacity and cycle performance of zinc ion batteries, and uses a method of in-situ etching of copper foil with a polysulfide precursor solution to prepare a Cu@Cu integrated current collector electrode material without a binder or a conductive agent. 31 S 16 The Cu@Cu 31 S 16 Positive electrode materials are used in the preparation of zinc ion batteries and their positive electrodes to improve the capacity and cycle performance of zinc ion batteries, including the following:
[0010] A zinc ion battery positive electrode material, the material specifically refers to Cu@Cu 31 S 16 The Cu@Cu composite material 31 S 16 The composite material includes a Cu current collector and a Cu 31 S 16 Positive electrode material.
[0011] A method for preparing a positive electrode material for a zinc ion battery comprises the following steps:
[0012] Step 1: Disperse Na2S·9H2O and sublimed sulfur in a mixed solution of methanol and water, and then stir the solution by ultrasonic vibration until it is completely dissolved to obtain an orange-yellow mixed solution, which is named as polysulfide etching solution;
[0013] Step 2: Punch and cut the copper foil into electrode sheets, use anhydrous ethanol to ultrasonically clean the surface to remove stains, and put it in an oven to dry;
[0014] Step 3: Apply the polysulfide etching solution obtained in step 1 to the surface of the copper foil prepared in step 2. After the reaction is complete, wash it with deionized water and put it into an oven for drying to obtain a positive electrode sheet with one side red and the other side black, which is named Cu@Cu 31 S 16 , the preparation of zinc ion battery positive electrode material is completed.
[0015] Preferably, the volume ratio of the methanol-water mixed solution in step 1 is 7:3.
[0016] Preferably, the mass ratio of Na2S·9H2O and sublimed sulfur in step 1 is 15:2.
[0017] A zinc ion battery positive electrode, wherein the Cu@Cu 31 S 16 The composite material serves as the positive electrode active material and the current collector.
[0018] The invention discloses an application of a zinc ion battery positive electrode in preparing a zinc ion battery.
[0019] Compared with the prior art, the present invention provides a zinc ion battery positive electrode material and a preparation method thereof, which has the following beneficial effects:
[0020] (1) The present invention provides a positive electrode material for a zinc ion battery and a preparation method thereof, wherein the positive electrode material specifically refers to Cu@Cu 31 S 16 Composite materials, Cu@Cu 31 S 16 The composite material includes a Cu current collector and a Cu 31 S 16 The positive electrode material has the following characteristics: ①Cu 31 S 16 The inherent properties will not produce Jahn-Teller distortion, which is conducive to the stable cycle of the electrode; ②Cu 31 S 16 It has excellent electronic / ionic conductivity and moderate voltage stability, showing metallic characteristics and better conductivity; ③Cu@Cu 31 S 16 No binder or conductive agent, which saves costs and simplifies the process; ④Cu 31 S 16 It is not only an efficient positive electrode material for zinc ion batteries, but also an excellent positive electrode material for hydrogen protons. Based on the above characteristics, the present invention applies the above positive electrode material to the preparation of zinc ion batteries, so that the battery rate performance and cycle performance are significantly improved.
[0021] (2) The experimental results show that under the conditions of constant temperature of 25 °Ϲ and neutral electrolyte of 2 M ZnSO4, the voltage range of 0.3-0.9 V is 0.5 A g -1 The current density of 0.2 A g was used for charge and discharge test, and the discharge capacity was still maintained after 1000 cycles. -1 At a current density of 1.5 volts, the first discharge capacity of the battery using the zinc ion battery positive electrode material of the present invention reaches 556 mAhg. At a constant temperature of 25 °Ϲ, in the acidic electrolyte of 2 M ZnSO4+0.001 M H2SO4, 2 M ZnSO4+0.002 M H2SO4, 2 M ZnSO4+0.004M H2SO4, in the voltage range of 0.2-1.05 V, the battery has a discharge capacity of 556 mAhg. -1 The current density of 0.5 A g -1 At a current density of 1.37 W / m, in the acidic electrolyte of 2 M ZnSO4+0.001 M H2SO4, 2 M ZnSO4+0.002 M H2SO4, and 2 M ZnSO4+0.004 M H2SO4, the first discharge specific capacity of the battery using the zinc ion battery positive electrode material of the present invention reached 716.7, 951.4, and 1161.7 mA h g, respectively. -1 At the same time, the zinc-ion battery positive electrode material has the advantages of low production cost and simple operation, and can be industrially mass-produced. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The Cu@Cu prepared in Example 1 of the present invention 31 S 16 SEM images of the composite material;
[0023] Figure 2 The Cu@Cu prepared in Example 1 of the present invention 31 S 16 Elemental distribution diagram of Cu and S in the composite material;
[0024] Figure 3 The Cu@Cu prepared in Example 1 of the present invention 31 S 16 Physical picture of positive electrode;
[0025] Figure 4 The Cu@Cu prepared in Example 1 of the present invention 31 S 16 XRD patterns of composite materials and standard cards;
[0026] Figure 5 The Cu@Cu prepared in Example 1 of the present invention 31S 16 When used as positive electrode material for zinc ion batteries, -1 Discharge capacity cycle diagram at current density;
[0027] Figure 6 The Cu@Cu prepared in Example 1 of the present invention 31 S 16 When used as the positive electrode material for zinc ion batteries, the electrolyte solution is 2 M ZnSO4+0.001 M H2SO4, 2 M ZnSO4+0.002 M H2SO4, and 2 M ZnSO4+0.004 M H2SO4. -1 Discharge specific capacity diagram at current density. DETAILED DESCRIPTION
[0028] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments.
[0029] The present invention provides a positive electrode material for zinc ion batteries, specifically Cu@Cu 31 S 16 Composite material, comprising a Cu current collector and a Cu 31 S 16 Cathode material, Cu@Cu 31 S 16 The color of the composite material is copper metal red on one side and Cu on the other side. 31 S 16 The positive electrode material is black.
[0030] The preparation method of the above-mentioned zinc ion battery positive electrode material specifically comprises the following steps:
[0031] Step 1: Disperse Na2S·9H2O and sublimed sulfur in a mixed solution of methanol and water, and then stir the solution by ultrasonic vibration until it is completely dissolved to obtain an orange-yellow mixed solution, which is named as polysulfide etching solution;
[0032] Step 2: Punch and cut the copper foil into electrode sheets, use anhydrous ethanol to ultrasonically clean for 10 minutes to remove surface stains, and put it in an oven to dry;
[0033] Step 3: Apply the polysulfide etching solution obtained in step 1 to the prepared copper foil surface, wait for it to react completely, wash it with deionized water and put it into an oven for drying to obtain a positive electrode sheet with one side red and the other side black, named Cu@Cu 31 S 16 ;
[0034] The zinc ion battery positive electrode material obtained above is applied to a zinc ion battery, and the steps are as follows:
[0035] The positive electrode sheet, commercial glass fiber separator, and metal zinc foil were assembled into button cells in a glove box in this order for testing the electrochemical performance.
[0036] The invention is further described in detail below in conjunction with specific examples, and the raw materials involved in the examples are all commercially available.
[0037] Embodiment 1:
[0038] Preparation of Cu@Cu 31 S 16 Cathode Materials
[0039] (1)Cu@Cu 31 S 16 Cathode Materials
[0040] A 1 mm thick copper foil was punched and cut into 12 mm diameter electrode sheets, and then ultrasonically cleaned with anhydrous ethanol for 10 minutes to remove surface stains and dried in an oven. 4.8 g Na2S·9H2O and 0.64 g sublimated sulfur were dispersed in 10 ml 70% methanol aqueous solution, and then ultrasonically stirred until completely dissolved. It was an orange-yellow liquid named polysulfide etching solution; 50 microliters of polysulfide etching solution was applied to the prepared copper foil surface, and after it was completely reacted, it was washed with deionized water and dried in an oven to obtain a positive electrode with one side red and the other side black.
[0041] The Cu@Cu prepared above 31 S 16 The positive electrode is applied to the zinc ion battery, the steps are as follows:
[0042] According to Cu@Cu 31 S 16 The positive electrode sheet, commercial PP separator, electrolyte, and metal zinc foil were assembled into button cells in a glove box to test the electrochemical performance.
[0043] The experimental results show that at a constant temperature of 25 °Ϲ, in a neutral electrolyte of 2 M ZnSO4, the voltage range of 0.3-0.9 V is 0.5 A g -1 The current density of 0.2 A g was used for charge and discharge test, and the discharge capacity was still good after 1000 cycles. -1 At a current density of 1.54 Å, the first discharge capacity of the battery using the zinc ion battery positive electrode material of the present invention reaches 556 mAh g -1At a constant temperature of 25 °Ϲ, in the acidic electrolyte of 2 M ZnSO4+0.001 M H2SO4, 2 M ZnSO4+0.002 M H2SO4, 2 M ZnSO4+0.004 M H2SO4, the voltage range was 0.2-1.05 V, and the reaction was carried out at 0.5 A g -1 The current density of 0.5 A g -1 At a current density of 1.37 W / m, under the conditions of acidic electrolyte 2 M ZnSO4 + 0.001 M H2SO4, 2 M ZnSO4 + 0.002 M H2SO4, and 2 M ZnSO4 + 0.004 M H2SO4, the first discharge specific capacity of the battery using the zinc ion battery positive electrode material of the present invention reached 716.7, 951.4, and 1161.7 mAhg, respectively. -1 The results are shown in Table 1.
[0044] Table 1
[0045]
[0046] The prepared Cu@Cu 31 S 16 The composite materials were analyzed and characterized as follows:
[0047] See also Figure 1 , Figure 1 For the prepared Cu@Cu 31 S 16 Scanning electron microscope photos of the material clearly show that a large number of nanorods grow on the Cu surface. Nanorods can increase the specific surface area and expose more active sites, which can provide embedding channels for hydrogen protons and zinc ions, thereby improving battery rate performance and cycle performance.
[0048] See also Figure 2 , Figure 2 For the prepared Cu@Cu 31 S 16 The element distribution diagram of Cu and S in the composite material shows that each element is evenly distributed.
[0049] See also Figure 3 , Figure 3 For the prepared Cu@Cu 31 S 16 The photo of the positive electrode shows the macroscopic appearance of the positive electrode.
[0050] See also Figure 4 , Figure 4 The Cu@Cu prepared in Example 31 S 16XRD patterns of the composite material and standard card show that Cu@Cu 31 S 16 The diffraction peaks of the Cu@Cu prepared in this embodiment of the present invention are highly consistent with the standard card, which shows that 31 S 16 Possessing high purity and high crystallinity.
[0051] See also Figure 5 , Figure 5 For the prepared Cu@Cu 31 S 16 When used as positive electrode material for zinc ion batteries, -1 The discharge capacity cycle diagram at the current density of . It can be seen from the figure that after 1000 cycles, the discharge capacity is still maintained very well.
[0052] See also Figure 6 , Figure 6 For the prepared Cu@Cu 31 S 16 When used as the positive electrode material of zinc ion batteries, the electrolyte solution is 2M ZnSO4+0.001M H2SO4, 2M ZnSO4+0.002M H2SO4, 2M ZnSO4+0.004M H2SO4. -1 The discharge capacity diagram at the current density of . It can be seen from the figure that the addition of hydrogen protons not only does not affect the discharge capacity of zinc ions, but also greatly improves the discharge platform and discharge capacity of the battery.
[0053] In summary, the Cu@Cu prepared by the zinc ion battery positive electrode material and the preparation method thereof proposed in the present invention 31 S 16 The composite positive electrode material is applied to zinc ion batteries, and the rate performance and cycle performance of zinc ion batteries are significantly improved.
[0054] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A method for preparing a positive electrode material for a zinc ion battery, characterized in that: The material specifically refers to Cu@Cu 31 S 16 The Cu@Cu composite material 31 S 16 The composite material includes a Cu current collector and a Cu 31 S 16 Cathode material; The preparation method comprises the following steps: Step 1: Disperse Na2S·9H2O and sublimed sulfur in a mixed solution of methanol and water, and then stir the solution by ultrasonic vibration until it is completely dissolved to obtain an orange-yellow mixed solution, which is named as polysulfide etching solution; Step 2: Punch and cut the copper foil into electrode sheets, clean them with anhydrous ethanol ultrasonically for 10 minutes to remove surface stains, and put them in an oven to dry; Step 3: Apply the polysulfide etching solution obtained in step 1 to the surface of the copper foil prepared in step 2. After the reaction is complete, wash it with deionized water and put it into an oven for drying to obtain a positive electrode sheet with one side red and the other side black, which is named Cu@Cu 31 S 16 , the preparation of zinc ion battery positive electrode material is completed.
2. The method for preparing a positive electrode material for zinc ion batteries according to claim 1, wherein The volume ratio of the methanol-water mixed solution in step 1 is 7:
3.
3. The method for preparing a positive electrode material for zinc ion batteries according to claim 1, wherein The mass ratio of Na2S·9H2O and sublimed sulfur in step 1 is 15:
2.
4. the application of the positive electrode material prepared by the positive electrode material preparation method for zinc ion battery as claimed in claim 1 on the preparation of zinc ion battery positive pole, is characterized in that, The Cu@Cu 31 S 16 The composite material serves as the positive electrode active material and the current collector.
5. Application of a zinc ion battery positive electrode prepared from zinc ion batteries as claimed in claim 4.
Citation Information
Patent Citations
Application of copper sulfide material in battery positive electrode material, electrode and battery
CN114914442A